2017
DOI: 10.26694/2448-0002.vl2iss1pp1-5
|View full text |Cite
|
Sign up to set email alerts
|

Leucócitos totais em cães com gastroenterite hemorrágica tratados por autohemoterapia

Abstract: A gastroenterite hemorrágica (GEH) é comum em cães jovens com sinais clínicos característicos como vômitos e diarreia. Entre as principais causas desse tipo de enfermidade estão as viroses como parvovirose e cinomose. O tratamento de GEH geralmente é sintomático com índice de recuperação em torno de 70%. A autohemoterapia é uma técnica em que se utiliza a administração de sangue autólogo por via intramuscular, a fim de estimular o sistema imunológico. Com o objetivo de avaliar a resposta leucocitária em cães a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The leukocyte level can be used to establish the prognosis against infection so that the increase in leukocytes during the hospitalization time results in increased survival of the animals ( Lopes et al, 2017 ). However, the blood counts of the surviving animals 24 hours after treatment was not elucidative when related to the clinical signs evaluated during the research, probably due to the short interval between exams and reduced experimental N.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The leukocyte level can be used to establish the prognosis against infection so that the increase in leukocytes during the hospitalization time results in increased survival of the animals ( Lopes et al, 2017 ). However, the blood counts of the surviving animals 24 hours after treatment was not elucidative when related to the clinical signs evaluated during the research, probably due to the short interval between exams and reduced experimental N.…”
Section: Discussionmentioning
confidence: 99%
“…The leukocyte level can be used to establish the prognosis against infection so that the increase in leukocytes during the hospitalization time results in increased survival of the animals (Lopes et al, 2017). However, the blood counts of the surviving animals 24 hours after treatment was not elucidative when related to the clinical signs evaluated during the research, probably due to the short interval between exams and reduced experimental N. Mantione and Otto (2005) analyzed 77 cases of canine parvovirus in which the mean hospitalization time was 6 days, while Kalli et al (2010) showed that the mean was 5.7 (± 2.5) days for surviving animals in their research.…”
Section: /9mentioning
confidence: 99%